Askins Tumor - A Rare Case Report and Literature Review (Journal of Medicine, 2013)
Askins Tumour (Synonym: Primitive Neuro-Ectodermal Tumor) is a rare neoplasm of the chest wall. In 1979 Askin and Rosai described an unique clinicopathological entity, characterised as a malignant small-cell tumour of the soft tissues of the chest wall in childhood and adolescence. We report on a case of a 30-year old male who had a massive tumour in the left thorax. The clinical symptoms were cough and increasing dyspnoea. The tumour was revealed as a Primitive Neuro-Ectodermal Tumor (PNET) compatible with ASKINs Tumor by CT-guided fine needle aspiration. Immunohistochemical studies showed positive staining for CD99. In our case , radiotherapy followed by chemotherapy was given. Microscopy and immunohistological stain of the specific markerneuron-specific enolaseare essential. Multimodal treatment allows a long-term survival, but often the prognosis is variable.DOI: http://dx.doi.org/10.3329/jom.v14i1.14588 J MEDICINE 2013; 14 : 94-97